Analisis Kompensasi Kerja terhadap Peningkatan Kinerja Karyawan: Kajian Literasi - Dhafa Herlambang Wisanggeni; Daffa Dwi Saputra; Teguh Prasetio (Pusat Riset dan Inovasi Nasional, 2024)
This research analyzes the relationship between work compensation and employee performance, highlighting how providing adequate compensation can influence motivation and job satisfaction. Using a literature review approach, this article explores the theories of work compensation and the factors that influence employee performance. The results show that compensation plays an important role in improving productivity, motivation and job satisfaction. A fair, competitive, and performance-based compensation strategy is proven to increase employee loyalty and commitment to the organization. This article confirms the importance of strategic compensation design to support organizational sustainability and increased competitiveness in the labor market.